Model Interaksi School Well-Being dan Burnout Guru dalam Konteks Hybrid Learning: Dukungan Sosial sebagai Faktor Protektif - Hidayatul Musthofa; Muh Fuad Firmansyah (https://journal.metanusantara.com/pedagogia, 2025)
The implementation of post-pandemic hybrid learning has created complex challenges for teachers, potentially triggering burnout while schools are tasked with ensuring educator well-being (school well-being). This explanatory quantitative research aims to analyze the interaction between school well-being and teacher burnout in the context of hybrid learning, exploring the role of social support as a protective factor. Primary data was collected through standardized questionnaires from 250 high school teachers in Central Java with at least one year of experience in hybrid learning. The results revealed a significant and strong negative relationship between school well-being and burnout. The key finding of this study is that social support acts as a significant moderator, strengthening the protective effect of school well-being against burnout. Further analysis indicated that support from peers was more dominantly perceived compared to support from supervisors and the institution. This research concludes that investing in building a structured social support system, particularly from school leadership, is a strategic step to maximize the benefits of school well-being in preventing teacher burnout in the hybrid learning era.